Human Norovirus NTPase Antagonizes Interferon-β Production by Interacting With IkB Kinase ε - Zheng, Zifeng; Li, Yuncheng; Zhang, Mudan; Liu, Yalan; Fu, Ming; Gong, Sitang; Hu, Qinxue (Frontiers in Microbiology, 2021)
Human norovirus (HuNoV) is the leading cause of epidemic acute gastroenteritis worldwide. Type I interferons (IFN)-α/β are highly potent cytokines that are initially identified for their essential roles in antiviral defense. It was reported that HuNoV infection did not induce IFN-β expression but was controlled in the presence of IFN-β in human intestinal enteroids (HIEs) and a gnotobiotic pig model, suggesting that HuNoV has likely developed evasion countermeasures. In this study, we found that a cDNA clone of GII.4 HuNoV, the predominantly circulating genotype worldwide, inhibits the production of IFN-β, and identified the viral NTPase as a key component responsible for such inhibition. HuNoV NTPase not only inhibits the activity of IFN-β promoter but also the mRNA and protein production of IFN-β. Additional studies indicate that NTPase inhibits the phosphorylation and nuclear translocation of IRF-3, leading to the suppression of IFN-β promoter activation. Mechanistically, NTPase interacts with IKKε, an important factor for IRF-3 phosphorylation, and such interaction blocks the association of IKKε with unanchored K48-linked polyubiquitin chains, resulting in the inhibition of IKKε phosphorylation. Further studies demonstrated that the 1-179 aa domain of NTPase which interacts with IKKε is critical for the suppression of IFN-β production. Our findings highlight the role of HuNoV NTPase in the inhibition of IFN-β production, providing insights into a novel mechanism underlying how HuNoV evades the host innate immunity.